Analysis of the public catering market in the Penza region - E. V. Kuznetsova; I. A. Strekalovsky (Вестник университета)
The article considers current situation and structure of the catering market in the Penza region and identifies the market leaders. The main player in the market in terms of revenue and number of catering outlets is the fast food sector. The main challenges faced by restaurateurs in 2022–2023 have been described. Geopolitical challenges have not bypassed this sector and caused changes in the market structure, influencing financial results and operational processes. The article presents a retrospective of the market development based on statistical data and extrapolates trends for a three-year period. The article presents the results of an expert survey of top restaurant managers on the problems faced by existing restaurateurs and identifies opportunities for the sector development. The most significant operational difficulties are the lack of line staff and the change in business economics caused by an increase in the raw materials cost.   The relevance of the study is to understand current market situation and its changes in recent years for further planning of market actions considering the experts’ opinion working in the field and trends that are emerging in the market.